The challenges of making family at a distance. Some reflections on migrations and family dynamics in Cape Verde - de Souza Lobo, Andréa (2020)
The article addresses the relationships between migrations, gender, and family dynamics, focusing on the Creole society of Cape Verde. Based on field research data from Boa Vista Island, from which many women have emigrated to Italy to work as housemaids, I reflect on the constructions of family dynamics in a territorial and relational space that is not restricted to people who reside in physical proximity. In a process that I denominate making family, networks of support and solidarity to which people constantly turn, people come and go between the two localities. This is the result of long-term planning that obeys both the Cape Verdean logic that to grow it is necessary to leave and the adaptability of projects of mobility to the labor market and Italian immigration law.